“TUMBLR TOLD ME…”: THE POLITICAL AND METHODOLOGICAL SIGNIFICANCE OF CONCEPTUALIZING SOCIAL MEDIA PLATFORMS AS LIVING ACTORS - Morgenstern, Michelle (AoIR Selected Papers of Internet Research, 2020)
This paper takes up the question of how “platform” can be understood when it comes to studies of digital discourse. I posit that this is an empirical and ethnographic question, rather than a purely theoretical one. Regardless of how scholars theorize social media platforms and other technologies, the people interacting with those technologies already have their own emic conceptualizations of what that technology is and how it functions and those understandings shape their social media experiences. This paper aims to explore the stakes of such local conceptualizations. I argue that many of tumblr.com’s most active users conceptualize the social media platform as a living actor — a dynamic and agentive entity with whom these young people interact, rather than a space on which they interact or a medium through which they interact. Attending to this particular understanding of Tumblr-as-actor is crucial because it has so intimately shaped the processes by which my research participants have come to take up new political-ethical commitments and identities through their engagement with the platform. However, I suggest that new methodological approaches for the study of digital discourse are required if scholars are to truly take seriously an understanding of platform as agentive figure. To this end, I argue for the use of audio-visual screen capture technologies that concurrently record the content on a screen alongside the bodies of users themselves for analyzing in-the-moment interactions between user and platform.